2009
DOI: 10.22266/ijies2009.1231.05
|View full text |Cite
|
Sign up to set email alerts
|

Detection of NS Resource Record DNS Resolution Traffic, Host Search, and SSH Dictionary Attack Activities

Abstract: We carried out an entropy study on the DNS query traffic from the Internet to the top domain DNS server in a university campus network through January 1st to March 31st, 2009. The obtained results are: (1) We observed a difference for the entropy changes among the total-, the A-, and the PTR resource records (RRs) based DNS query traffic from the Internet through January 17th to February 1st, 2009. (2) We found the large NS RR based DNS query traffic including only a keyword "." in the total inbound DNS query … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…From the experimental results, we intend to continue improving our method with the ultimate goal of being able to detect the dictionary attacks against many services to enable secure networks. Thames et al (Thames et al, 2008) log file high low yes yes no no Su et al (Su et al, 2011) log file high low yes yes no no Sperotto et al (Sperotto et al, 2009) traffic low not clear yes no no no Takemori et al (Takemori et al, 2009) traffic low high yes no no no Our work traffic low moderate yes yes yes yes j o u r n a l o f i n f o r m a t i o n s e c u r i t y a n d a p p l i c a t i o n s x x x ( 2 0 1 4 ) 1 e1 1…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the experimental results, we intend to continue improving our method with the ultimate goal of being able to detect the dictionary attacks against many services to enable secure networks. Thames et al (Thames et al, 2008) log file high low yes yes no no Su et al (Su et al, 2011) log file high low yes yes no no Sperotto et al (Sperotto et al, 2009) traffic low not clear yes no no no Takemori et al (Takemori et al, 2009) traffic low high yes no no no Our work traffic low moderate yes yes yes yes j o u r n a l o f i n f o r m a t i o n s e c u r i t y a n d a p p l i c a t i o n s x x x ( 2 0 1 4 ) 1 e1 1…”
Section: Resultsmentioning
confidence: 99%
“…Sperotto et al (2009) showed that such attacks typically consist of three phases, and the authors represented their behaviors at flow level by Hidden Markov Model. Takemori et al (2009) discovered a significant upsurge in the number of PTR resource records in DNS traffic while the attacks were underway. This approach limits the above costs because its requirement is to only capture traffic at a few observation points.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Hellemons et al [10] showed that such attacks typically consist of three phases, and the authors represented their behaviors at the flow level by using a hidden Markov model. Takemori et al [11] discovered a significant upsurge in the number of pointer (PTR) resource records in DNS traffic while attacks were underway. To resolve the problems of these studies, we proposed a new approach [12] that detects dictionary attacks and their success or failure.…”
Section: Related Work and Limitationsmentioning
confidence: 99%
“…Previously, on the other hand, we reported that the DNS traffic and entropy based detection technologies of the inbound-and outbound SSH dictionary attacks in the campus network [9][10][11][12]. The DNS based detection system has a merit which observes only the DNS query request packet traffic between the DNS server and its clients i.e.…”
Section: Introductionmentioning
confidence: 99%